Pengaruh Media Gambar dalam Meningkatkan Hasil Belajar Peserta Didik Paket B pada Mata Pelajaran PPKN di UPT SKB Gresik - Asyari, Muhammad Dwiky Hasyim; Susilo, Heryanto (J+PLUS UNESA, 2024)
This research aims to determine the effect of using image media on the learning outcomes of package B students in PPKN subjects at UPT SKB Gresik. This type of research uses quantitative methods with the research type Pre-Experimental One-Group Pretest-Post test Design. The sample for this research was 7 package B class VIII students. The data collection technique used was questionnaires, tests (pretest and post test), observation and documentation. Data analysis used used questionnaire percentages, Normality Test, Homogeneity Test, and Hypothesis Test using parametric statistics, namely the paired sample t test. The research results show that the average value of learning outcomes has increased, with the average value of pretest results being 34, which if the learning outcome scores are categorized, 2 students get the medium category, and 5 students get the low category. After carrying out the post test, the learning outcome score increased with an average score of 64, where if categorized, 3 students got the high category, and 4 students got the medium category. The results of the pretest and posttest data were then shown by hypothesis testing using the paired sample t test, which obtained a value of 0.000 < 0.05, which means there is an influence of the use of learning media in the form of images on the learning outcomes of package B students in PPKN subjects at UPT SKB Gresik.